2012
DOI: 10.1259/bjr/63355844
|View full text |Cite
|
Sign up to set email alerts
|

Mechanism of radioprotection by δ-tocotrienol: pharmacokinetics, pharmacodynamics and modulation of signalling pathways

Abstract: Objective: The objective of this study was to investigate the correlation between in vivo d-tocotrienol (DT3) pharmacokinetics, pharmacodynamics and radiation protection, and to evaluate the effect of DT3 pre-treatment on radiation-induced alterations in apoptotic and autophagic pathways. Methods: We evaluated pharmacokinetics (plasma, 0.5 to 12 h) and pharmacodynamics (peripheral blood indices; day 3, 7, 10 and 14) after a single subcutaneous injection of 300 mg kg -1 DT3 in unirradiated CD2F1 mice. Next, we … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
39
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(41 citation statements)
references
References 35 publications
1
39
0
1
Order By: Relevance
“…Radiotherapy, second only to surgery, is used with 80% of patients as one of the most effective modalities for the treatment and cure of neoplastic diseases (Nair et al, 2001;Parihar et al, 2007;Satyamitra et al, 2012). Ionizing radiation triggers a series of events starting from generation of reactive oxygen species (ROS).…”
Section: Introductionmentioning
confidence: 99%
“…Radiotherapy, second only to surgery, is used with 80% of patients as one of the most effective modalities for the treatment and cure of neoplastic diseases (Nair et al, 2001;Parihar et al, 2007;Satyamitra et al, 2012). Ionizing radiation triggers a series of events starting from generation of reactive oxygen species (ROS).…”
Section: Introductionmentioning
confidence: 99%
“…These changes are associated with activation of mRNA translation regulator eIF4E and ribosomal protein S6, which are responsible for cell survival and growth. DT3 has also been shown to suppress apoptotic death pathways and modulate autophagic markers (Satyamitra et al, 2012). Further study is needed to understand exact mechanism of G-CSF induction by DT3.…”
Section: Discussionmentioning
confidence: 99%
“…DT3 has been shown to have both radioprotective (administered before radiation exposure) and radiomitigative (administered after radiation exposure) efficacy (Satyamitra et al, 2011). Recently, delta-tocotrienol (DT3) was demonstrated to reduce activation of caspase-8, caspase-3, and caspase-7 while increasing autophagy-related beclin-1 expression in irradiated bone marrow cells (Satyamitra et al, 2012). DT3 also has been reported to increase cell survival and regeneration of hematopoietic microfoci and lineage -/Sca-1 + /c-Kit + stem and progenitor cells in irradiated mouse bone marrow cells (Li et al, 2010).…”
mentioning
confidence: 99%
“…Pharmacokinetics of DT3 was evaluated previously in CD2F1 mice. 21 Authors determined the plasma concentration of a single dose of DT3 (300 mg/kg) administered sc in CD2F1 mice. The peak plasma concentration (C max ) of DT3 was 195 mmol/L 1 hour after injection (T max ).…”
Section: Introductionmentioning
confidence: 99%
“…The plasma half-life (t 1/2 ) was 1.8 hours, and DT3 was cleared from plasma within 12 hours after administration. 21 Gamma-tocotrienol (GT3, Figure 1B) also exhibits potent radioprotective activity following whole-body g-radiation exposure in a mouse model. It was previously demonstrated that GT3 provided higher radioprotection than alpha-tocopherol.…”
Section: Introductionmentioning
confidence: 99%